Long-term Limnological Research and Monitoring at Crater Lake, Oregon A benchmark study of a deep and exceptionally clear montane caldera lake - Larson, G.L; Collier, R.W; Buktenica, M.W (Developments in Hydrobiology, 2007)
Crater Lake is located in the caldera of Mount Mazama in Crater Lake National Park, Oregon. The lake has a surface area of about 53 km2 at an elevation of 1882 m and a maximum depth of 594 m - seventh deepest in the world. Limited studies of this ultraoligotrophic lake conducted between 1896 and 1981, lead to a 10-year limnological study to evaluate any potential degradation of water quality. No long-term variations in water quality were observed that could be attributed to anthropogenic activity. Building on the success of this study, a permanent limnological program has been established with a long-term monitoring program to insure a reliable data base for use in the future. Of equal importance, this program serves as a research platform to develop and communicate to the public a better understanding of the coupled biological, physical, and geochemical processes in the lake and its surrounding environment. This special volume represents our current state of knowledge of the status of this pristine ecosystem including its special optical properties, algal nutrient limitations, pelagic bacteria, and models of the inter-relationships of thermal properties, nutrients, phytoplankton, deep-water mixing, and water budgets.